2015
DOI: 10.1159/000373937
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Suppresses Doxorubicin-Induced Cardiotoxicity by Regulating the Oxidative Stress and p38MAPK Pathways

Abstract: Background: SIRT1, which belongs to the Sirtuin family of NAD-dependent enzymes, plays diverse roles in aging, metabolism, and disease biology. It could regulate cell survival and has been shown to be a protective factor in heart function. Hence, we verified the mechanism by which SIRT1 regulates doxorubicin induced cardiomyocyte injury in vivo and in vitro. Methods: We analyzed SIRT1 expression in doxorubicin-induced neonatal rat cardiomyocyte injury model and adult mouse heart failure model. SIRT1 was over-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 26 publications
4
75
0
2
Order By: Relevance
“…Activation of SIRT1 not only suppresses apoptosis but also balances oxidative stress in the heart, while absence of SIRT1 triggers chronic inflammation, oxidative stress, and cell cycle arrest (Gu et al 2013). Further, Ruan et al (2015) demonstrated that SIRT1 expression was downregulated in doxorubicin-induced cardiomocyte injury, accompanied by elevated oxidative stress and cell apoptosis, and interestingly, SIRT1 is involved in the protection of the heart from doxorubicin-induced pathway, partly through the inhibition of the p38 MAPK pathway.…”
Section: The Sirtuin Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of SIRT1 not only suppresses apoptosis but also balances oxidative stress in the heart, while absence of SIRT1 triggers chronic inflammation, oxidative stress, and cell cycle arrest (Gu et al 2013). Further, Ruan et al (2015) demonstrated that SIRT1 expression was downregulated in doxorubicin-induced cardiomocyte injury, accompanied by elevated oxidative stress and cell apoptosis, and interestingly, SIRT1 is involved in the protection of the heart from doxorubicin-induced pathway, partly through the inhibition of the p38 MAPK pathway.…”
Section: The Sirtuin Familymentioning
confidence: 99%
“…In addition, several sirtuins play additional roles in metabolic homeostasis (Choi and Mostoslavsky 2014). Based on their enzymatic activities, sirtuins can also play a pivotal role in oxidative stress modulation (Conti et al 2015;Li et al 2015;Zhang et al 2015). Sirtuins are intimately linked to the cellular response to oxidative stress (Merksamer et al 2013); they might be activated during redox stress and may modulate crucial responses, including the adaptation to hypoxia and ameliorating ROS-induced pathologies (Webster et al 2012).…”
Section: The Sirtuin Familymentioning
confidence: 99%
“…reporting that SIRT1 could promote cardiomyocyte cell survival following acute doxorubicininduced oxidative burden by attenuating ROS production (152). Thus there may be an optimal activity level and time-specific application of sirtuin function to attenuate contributing factors of vascular aging.…”
Section: Sirt1mentioning
confidence: 99%
“…The excessive caspase-3 activity induced cell apoptosis in various types of cells [11][12][13]. Ox-LDL induced cells apoptosis via eliciting the caspase-3 activity [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%